Low-cost decorative antifouling imitation stone material and preparation method thereof

By using cementitious materials, active materials, aggregates and additives in the production process of artificial stone, as well as the application of antifouling coatings, the existing artificial stone has been solved, and artificial imitation stone materials with low cost, high performance and good decorative effects have been achieved.

CN119528502APending Publication Date: 2025-02-28JIANGXI CONSTR GRP NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410588538.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-13
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing artificial stone production process is complex, has high cost, insufficient durability and anti-fouling capabilities, making it difficult to meet the market's demand for low-cost, ultra-high performance and good decorative effects.

Method used

By combining cementitious materials, active materials, aggregates and additives in proportion, and using anti-fouling coatings to enhance the surface decorativeness and anti-fouling performance after mixing and forming, artificial imitation stone materials with low cost, ultra-high performance, good decorative effect and strong anti-fouling ability were developed.

Benefits of technology

It has achieved artificial stone with low production cost, simple process, ultra-high performance, durability and strong anti-fouling ability. The cost is only one-half of natural stone. The decorative effect is comparable to that of natural stone and has excellent anti-fouling and anti-microbial ability on the surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

The invention provides an artificial stone and a manufacturing method thereof, and the artificial stone comprises the following components in parts by mass: 400-450 parts of a cementing material, 80-180 parts of an active material, 530-710 parts of aggregate, 80-100 parts of water, 10-20 parts of an additive and 0.05-0.1 part of a coating. The preparation method comprises the following steps: proportionally adding the cementing material, the active material and the aggregate into a stirrer, uniformly stirring and mixing, weighing the mixing water and the additive according to the corresponding parts by mass, adding into the prepared mixed powder, and mechanically stirring by using the stirrer according to the set time. The preparation method comprises the following steps: continuously and uniformly mixing the raw materials, injecting the mixture into a mold of a specification model after the raw materials are continuously and uniformly mixed and have good fluidity, carrying out self-leveling and vibration until no bubble overflows, carrying out mold removal after the mold removal strength is reached, putting the product into a pre-curing chamber for pre-curing, polishing the surface of the product after the pre-curing is completed, and finally spraying an inorganic glaze self-cleaning coating on the surface of the polished product to obtain the artificial stone. The artificial stone disclosed by the invention has the advantages of low production cost, simple production process, ultra-high performance, good decoration performance, strong antifouling ability and the like, is close to natural stone and can be customized, and the excellent surface antifouling and antibacterial ability can keep the decoration effect for a long time and improve the durability. The artificial stone disclosed by the invention is rich in size, shape, color and variety, can better meet the market demand, reduces the mining of natural stone, and protects the green ecological environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to an artificial stone-like material for municipal engineering, roads and indoor and outdoor decoration and a manufacturing method thereof. Background Art

[0002] Existing natural stones have advantages such as ultra-high strength, high durability, strong machinability and unique color and texture, but there are problems such as reduced mining volume, environmental damage and non-renewable. Artificial stone is designed and manufactured according to the properties of natural stone and actual market demand. It has similar performance and texture shape as natural stone, and has richer shape and high degree of customization. The main disadvantages of artificial stone on the market are complex production process, high cost, poor durability and anti-fouling ability. In view of the situation, it is necessary to develop an artificial imitation stone material with simple production process, good economy, excellent durability and anti-fouling ability, and rich texture. Summary of the invention

[0003] The invention provides an artificial stone-like material and a manufacturing method thereof. The artificial stone-like material is prepared by designing a mix ratio of cementitious materials, active materials, aggregates and additives, mixing and casting the materials, and then using an antifouling coating to increase the surface decorative retention effect and antifouling performance. The artificial stone-like material has low cost, ultra-high performance, good decorative effect and strong antifouling ability.

[0004] The artificial stone provided by the present invention comprises, by weight, 400-450 parts of cementitious material, 80-180 parts of active material, 530-710 parts of aggregate, 80-100 parts of water, 10-20 parts of additives and 0.05-0.1 parts of coating.

[0005] Preferably, the cementitious material is 52.5 grade white silicate cement, wherein the whiteness is ≥90.0, the fineness (0.08 mm sieve residue rate, %) is ≤0.2%, and the water consumption at standard consistency is 26%.

[0006] Preferably, the active material comprises white silica ash and fly ash microspheres, wherein the white silica ash is 40-80 parts and the fly ash microspheres are 40-100 parts. The silica content in the white silica ash is ≥96%, the activity index is ≥110%, the specific surface area is ≥19000㎡ / kg, and the whiteness is ≥92; the average particle size of the fly ash microspheres is 6.3um, the content of spherical particles is ≥96%, and the water demand ratio is 85%.

[0007] Preferably, the above-mentioned aggregate includes white stone powder and crushed stone, wherein the white stone powder is 480-630 parts and the crushed stone is 50-80 parts. The main component of the white stone powder is granite, with a silicon dioxide content of not less than 65%, a quartz content of ≥20%, and a particle size between 0.075mm and 5mm; the crushed stone aggregate is basalt particles with a particle size between 5mm and 10mm.

[0008] Preferably, the above-mentioned additive is a polycarboxylic acid high-efficiency water-reducing agent, with a unit water reduction rate of ≥30%, a water bleeding rate ratio of ≤70%, and an air content of ≤6%.

[0009] Preferably, the above-mentioned inorganic coating is an inorganic transparent glaze self-cleaning coating.

[0010] The present invention provides a method for preparing the above-mentioned artificial stone, which comprises the following steps: (1) Adding cementitious materials, active materials and aggregates into a mixer in proportion and stirring and mixing them evenly to obtain mixed powder; (2) Weigh the mixing water and additives according to the corresponding mass parts; (3) adding the mixing water weighed in step (2) to the mixed powder obtained in step (1), and mechanically stirring the mixed powder using a stirrer for a set time. During the stirring process, adding additives according to a specified mass fraction, and continuously mixing until the mixed powder is uniform and has good fluidity, to obtain a mixed slurry; (4) Inject the mixed slurry into a mold of a specified size, self-level and vibrate until no bubbles overflow; (5) After reaching the demolding strength, demold the part and place it in the pre-curing room for pre-curing. After pre-curing, polish the surface of the part; (6) Spraying an inorganic glaze self-cleaning coating on the surface of the polished workpiece, and stacking the workpieces according to regulations, thereby obtaining the artificial stone-like material.

[0011] Preferably, the stirring time required for uniform mixing of the powders in step (1) is 10 minutes.

[0012] Preferably, the time interval between adding mixing water and additives in step (3) is as short as possible, and the overall stirring time of the slurry is controlled within 5 minutes.

[0013] Preferably, the vibration in step (4) should be uniform and the vibration time should be 10 to 20 seconds.

[0014] Preferably, the demoulding strength in step (5) is not less than 20 MPa, and the strength after pre-curing should be greater than or equal to 80% of the calculated strength. After polishing to completely expose the pattern, the surface is left to dry.

[0015] Preferably, the spraying in step (6) should be uniform without flow marks and without any touch damage to the surface.

[0016] Compared with existing artificial stones, the artificial stone of the present invention has the advantages of low production cost, simple production process, ultra-high performance, ultra-high durability, good decorative performance and strong anti-fouling ability, etc. The cost is only one-half of that of natural stone, the slurry can self-level and has good construction performance, the maximum strength can reach 139 MPa, which is close to that of natural stone, the decorative effect is comparable to that of natural stone and can be customized, and the excellent surface anti-fouling and antibacterial ability can maintain the decorative effect for a long time and improve durability. The artificial stone of the present invention has a rich variety of sizes, shapes and colors, can replace natural stone, better meet market demand, reduce the mining of natural stone, and protect the green ecological environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a process flow chart for preparing low-cost decorative antifouling stone-like materials. DETAILED DESCRIPTION

[0018] The present invention is further described in conjunction with specific examples. If no specific techniques or conditions are specified in the examples, the techniques described in the literature in the art or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0019] [Example 1] The artificial stone of the present invention provides a technical solution, which includes raw materials calculated by mass: 400 parts of 52.5 grade white silicate cement, 40 parts of white silica fume, 40 parts of fly ash microbeads, 480 parts of white stone powder, 50 parts of crushed stone, 80 parts of mixing water, 10 parts of additives, and 0.05 parts of coating.

[0020] Preparation method: (1) Add white silicate cement, white silica fume, fly ash microspheres, white stone powder and crushed stone into a mixer according to the mass proportion and stir for 5 minutes until the mixture is uniform to obtain a mixed powder; (2) Weigh the mixing water and additives according to the corresponding mass parts; (3) adding the mixing water and additives weighed in step (2) to the mixed powder obtained in step (1), and continuing to stir for 5 minutes using a stirrer. When the mixture is uniform and has good fluidity, stop stirring to obtain a mixed slurry; (4) Inject the mixed slurry into a standard mold, vibrate for 10 seconds while self-leveling, and no bubbles overflow; (5) Remove the mold and place it in the pre-curing room for 3 days. After the pre-curing is completed, polish the surface of the part; (6) Spraying an inorganic glaze self-cleaning coating with a thickness of about 2 mm on the surface of the polished workpiece, and stacking it according to regulations after drying, thereby obtaining the artificial stone-like material.

[0021] [Example 2] The artificial stone of the present invention provides a technical solution, which includes raw materials calculated by mass: 400 parts of 52.5 grade white silicate cement, 40 parts of white silica fume, 80 parts of fly ash microbeads, 520 parts of white stone powder, 55 parts of crushed stone, 85 parts of mixing water, 10 parts of additives, and 0.05 parts of coating.

[0022] Preparation method: (1) Add white silicate cement, white silica fume, fly ash microspheres, white stone powder and crushed stone into a mixer according to the mass proportion and stir for 5 minutes until the mixture is uniform to obtain a mixed powder; (2) Weigh the mixing water and additives according to the corresponding mass parts; (3) adding the mixing water and additives weighed in step (2) to the mixed powder obtained in step (1), and continuing to stir for 5 minutes using a stirrer. When the mixture is uniform and has good fluidity, stop stirring to obtain a mixed slurry; (4) Inject the mixed slurry into a standard mold, vibrate for 10 seconds while self-leveling, and no bubbles overflow; (5) Remove the mold and place it in the pre-curing room for 3 days. After the pre-curing is completed, polish the surface of the part; (6) Spraying an inorganic glaze self-cleaning coating with a thickness of about 2 mm on the surface of the polished workpiece, and stacking it according to regulations after drying, thereby obtaining the artificial stone-like material.

[0023] [Example 3] The artificial stone of the present invention provides a technical solution, which includes raw materials calculated by mass: 400 parts of 52.5 grade white silicate cement, 80 parts of white silica fume, 80 parts of fly ash microbeads, 560 parts of white stone powder, 60 parts of crushed stone, 90 parts of mixing water, 15 parts of additives, and 0.05 parts of coating.

[0024] Preparation method: (1) Add white silicate cement, white silica fume, fly ash microspheres, white stone powder and crushed stone into a mixer according to the mass proportion and stir for 5 minutes until the mixture is uniform to obtain a mixed powder; (2) Weigh the mixing water and additives according to the corresponding mass parts; (3) adding the mixing water and additives weighed in step (2) to the mixed powder obtained in step (1), and continuing to stir for 5 minutes using a stirrer. When the mixture is uniform and has good fluidity, stop stirring to obtain a mixed slurry; (4) Inject the mixed slurry into a standard mold, vibrate for 10 seconds while self-leveling, and no bubbles overflow; (5) Remove the mold and place it in the pre-curing room for 3 days. After the pre-curing is completed, polish the surface of the part; (6) Spraying an inorganic glaze self-cleaning coating with a thickness of about 2 mm on the surface of the polished workpiece, and stacking it according to regulations after drying, thereby obtaining the artificial stone-like material.

[0025] [Example 4] The artificial stone of the present invention provides a technical solution, which includes raw materials calculated by mass: 400 parts of 52.5 grade white silicate cement, 80 parts of white silica fume, 100 parts of fly ash microbeads, 580 parts of white stone powder, 65 parts of crushed stone, 95 parts of mixing water, 15 parts of additives, and 0.05 parts of coating.

[0026] Preparation method: (1) Add white silicate cement, white silica fume, fly ash microspheres, white stone powder and crushed stone into a mixer according to the mass proportion and stir for 10 minutes until the mixture is uniform to obtain a mixed powder; (2) Weigh the mixing water and additives according to the corresponding mass parts; (3) adding the mixing water and additives weighed in step (2) to the mixed powder obtained in step (1), and continuing to stir for 8 minutes using a stirrer. When the mixture is uniform and has good fluidity, stop stirring to obtain a mixed slurry; (4) Inject the mixed slurry into a standard mold, self-level and vibrate for 15 seconds without bubbles overflowing; (5) Remove the mold and place it in the pre-curing room for 3 days. After the pre-curing is completed, polish the surface of the part; (6) Spraying an inorganic glaze self-cleaning coating with a thickness of about 2 mm on the surface of the polished workpiece, and stacking it according to regulations after drying, thereby obtaining the artificial stone-like material.

[0027] [Example 5] The artificial stone of the present invention provides a technical solution, which includes the following raw materials calculated by mass: 450 parts of 52.5 grade white silicate cement, 80 parts of white silica fume, 100 parts of fly ash microbeads, 630 parts of white stone powder, 80 parts of crushed stone, 100 parts of mixing water, 20 parts of additives, and 0.1 parts of coating.

[0028] Preparation method: (1) Add white silicate cement, white silica fume, fly ash microspheres, white stone powder and crushed stone into a mixer according to the mass proportion and stir for 10 minutes until the mixture is uniform to obtain a mixed powder; (2) Weigh the mixing water and additives according to the corresponding mass parts; (3) adding the mixing water and additives weighed in step (2) to the mixed powder obtained in step (1), and continuing to stir for 10 minutes using a stirrer. When the mixture is uniform and has good fluidity, stop stirring to obtain a mixed slurry; (4) Inject the mixed slurry into a standard mold, self-level and vibrate for 20 seconds without any bubbles overflowing; (5) Remove the mold and place it in the pre-curing room for 3 days. After the pre-curing is completed, polish the surface of the part; (6) Spraying an inorganic glaze self-cleaning coating with a thickness of about 2 mm on the surface of the polished workpiece, and stacking it according to regulations after drying, thereby obtaining the artificial stone-like material.

[0029] Performance test: The artificial imitation stone material prepared by the present invention has the properties of ultra-high strength, ultra-high durability, good decorative effect and strong anti-fouling ability. The artificial imitation stone material prepared in Examples 1 to 5 is now subjected to performance testing. The specific test method is as follows:

[0030] Compressive and flexural strength: Tested according to the method specified in GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete".

[0031] Fluidity: Test according to the method specified in GB / T 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures".

[0032] Acid resistance: The acid resistance test is carried out according to the method specified in GB / T 9274-1988 "Determination of resistance of paints and varnishes to liquid media".

[0033] Alkali resistance: The alkali resistance test is carried out according to the method specified in GB / T 9265-2009 "Determination of alkali resistance of architectural coatings".

[0034] Stain resistance: The stain resistance test is carried out according to the method specified in GB / T 9780-2013 "Test method for stain resistance of architectural coatings".

[0035] Surface hardness: The surface hardness of the coating surface is measured in accordance with the method specified in GB / T 6739-2006 "Paints and varnishes - pencil method for determination of film hardness".

[0036] The specific test results are shown in the following table: Compressive strength (Mpa) Flexural strength (Mpa) Slump (mm) Acid resistance Alkali resistance Stain resistance Surface hardness Example 1 135 20 285 No defects such as blistering, falling off, cracking, etc. No blistering, cracking, peeling, or powdering 7% 6H Example 2 139 22 290 No defects such as blistering, falling off, cracking, etc. No blistering, cracking, peeling, or powdering 7% 7H Example 3 138 20 273 No defects such as blistering, falling off, cracking, etc. No blistering, cracking, peeling, or powdering 7% 6H Example 4 133 18 279 No defects such as blistering, falling off, cracking, etc. No blistering, cracking, peeling, or powdering 7% 6H Example 5 127 17 284 No defects such as blistering, falling off, cracking, etc. No blistering, cracking, peeling, or powdering 7% 6H

Claims

1. The artificial stone provided by the present invention, calculated by weight, comprises: 400-450 parts of cementitious materials, 80-180 parts of active materials, 530-710 parts of aggregates, 80-100 parts of water, 10-20 parts of additives, and 0.05-0.1 parts of coatings.

2. Preferably, the above-mentioned cementitious material is 52.5 grade white silicate cement, wherein the whiteness is ≥90.0, the fineness (0.08mm sieve residue rate, %) is ≤0.2%, and the water consumption for standard consistency is 26%.

3. Preferably, the above active materials include white silica ash and fly ash microspheres, wherein the white silica ash is 40-80 parts and the fly ash microspheres are 40-100 parts. The silicon dioxide content in the white silica ash is ≥96%, the activity index is ≥110%, the specific surface area is ≥19000㎡ / kg, and the whiteness is ≥92; the average particle size of the fly ash microspheres is 6.3um, the content of spherical particles is ≥96%, and the water demand ratio is 85%.

4. Preferably, the above-mentioned aggregate includes white stone powder and crushed stone, wherein the white stone powder is 480-630 parts and the crushed stone is 50-80 parts. The main component of the white stone powder is granite, with a silicon dioxide content of not less than 65%, a quartz content of ≥20%, and a particle size between 0.075mm and 5mm; the crushed stone aggregate is basalt particles with a particle size between 5mm and 10mm.

5. Preferably, the above-mentioned additive is a polycarboxylic acid high-efficiency water-reducing agent, with a unit water reduction rate ≥ 30%, a water bleeding rate ratio ≤ 70%, and an air content ≤ 6%.

6. Preferably, the above-mentioned inorganic coating is an inorganic transparent glaze self-cleaning coating.

7. The present invention provides a method for preparing the above-mentioned artificial stone, the preparation method comprising the following steps: (1) Adding cementitious materials, active materials and aggregates into a mixer in proportion and stirring and mixing them evenly to obtain mixed powder; (2) Weigh the mixing water and additives according to the corresponding mass parts; (3) adding the mixing water weighed in step (2) to the mixed powder obtained in step (1), and mechanically stirring the mixed powder using a stirrer for a set time. During the stirring process, adding additives according to a specified mass fraction, and continuously mixing until the mixed powder is uniform and has good fluidity, to obtain a mixed slurry; (4) Inject the mixed slurry into a mold of a specified size, self-level and vibrate until no bubbles overflow; (5) After reaching the demolding strength, demold the part and place it in the pre-curing room for pre-curing. After pre-curing, polish the surface of the part; (6) Spraying an inorganic glaze self-cleaning coating on the surface of the polished workpiece, and stacking the workpieces according to regulations, thereby obtaining the artificial stone-like material.

8. The preparation method according to claim 7, characterized in that: The stirring time required for uniform mixing of the powder in step (1) is 10 minutes; the time interval for adding mixing water and additives in step (3) is as short as possible, and the overall stirring time of the slurry is controlled within 5 minutes; the vibration in step (4) should be uniform, and the vibration time should be 10 to 20 seconds; the demolding strength in step (5) should not be less than 20 MPa, and the strength after pre-curing should be greater than or equal to 80% of the calculated strength. After polishing to completely expose the color, let the surface dry; the spraying in step (6) should be uniform without flow marks, and the surface should not be damaged by touch.